Varying time-course of effects of high frequency stimulation of sub-regions of the globus pallidus in patients with parkinson's disease. Issue 6 (June 2015) - Angeli, A.; Akram, H.; Zacharia, A.; Limousin, P.; Hariz, M.; Zrinzo, L.; Foltynie, T.
Abstract: Introduction: Deep brain stimulation of the globus pallidus can be a highly effective treatment for patients with Parkinson's disease (PD), experiencing Levodopa-induced-dyskinesia (LID). Stimulation programming can focus simply on eliminating dyskinesia, or can also attempt to relieve the rigidity, tremor or akinesia of PD itself. Methods: In this study, we explored whether additional benefit on the "off" symptoms and signs of PD, could be achieved in post-operative PD patients with good LID control, by making further adjustment to existing stimulation parameters directed towards the more superior electrode contacts, located in the Globus Pallidus pars externa (GPe). Results: Acutely, GPe-DBS led to clear improvement in the akinesia, rigidity and tremor of PD in the off-medication state compared with Globus Pallidus pars interna (GPi) DBS (p = 0.003), however this was accompanied by the development of off-medication dyskinesia. Combined GPi–GPe DBS allowed maintained improvement but without dyskinesia. Follow up of patients over the subsequent 6–12 weeks showed gradual loss of this initial improvement. Switching back to GPi-DBS alone provided greater improvement in off medication symptoms than had been observed using the same GPi-DBS setting, 6–12 weeks previously. Conclusions: Benefits on the off-medication symptoms of PD obtained acutely with GPe-DBS are in general not sustained. Similarly, the effects of GPi-DBS on the off medication symptoms of PD, can evolve over short periods of time presumably as a result of changes in network-wide neuronal plasticity. These clinical observations provide further insight into DBS mechanism of action, and can also help inform optimal methods of GPi-DBS programming. Highlights: We adjusted DBS parameters of 13 PD patients who had previously undergone GPi DBS to try and improve overall symptom control. We found that stimulation in the GPe located contacts improved the off symptoms of PD but provoked off medication dyskinesia. Combined with GPi stimulation, an advantage in control of off symptoms and dyskinesias could be achieved. At 6–12 weeks the additional benefit had lapsed, but restoring former GPi settings led to greater benefit than at baseline.